The development of resources and territories: what analysis for the Algerian date chain? - Nacera Arrouche (Journal of Excellence for Economics and Management Research, 2017)
In this paper we have tried to conduct a thorough reflection  around the following elements: territories, resources, and the role of public policies in a context of an Algerian territory rich in potentialities, particularly agricultural. These potentialities are likely to constitute a showcase of a local territory conveying a specific value enhancing on an international scale. We will also try in this work to show the interest for the Algerian decision-makers to adopt the chain strategy to make better use of the specific resources making the territory a particularity that it is necessary to make more visible.